Peran Kebijakan Merdeka Belajar Terhadap Pengembangan Karakter Dan Spiritualitas Mahasiswa di Sekolah Tinggi Teologi Kristen - Kristiani, Kristiani; Iyai, Yakobus; Purwonugroho, Daniel Pesah (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2023)
The Merdeka Belajar policy, supported by the Ministry of Education and Culture of the Republic of Indonesia, initiated a significant evolution in the educational framework, particularly at the College of Christian Theology. The initiative gives students the autonomy to choose courses, engage in project-based learning, and take part in extracurricular experiences, all aimed at cultivating students' character and spirituality. The implementation of Merdeka Belajar at the College of Christian Theology creates an environment conducive to the development of critical thinking skills, creativity, and an enriched understanding of theology and Christian principles. This study sought to investigate the consequences of this policy on the educational process, students' involvement in external activities, and their role in the formation of students' character and spirituality through a descriptive qualitative methodology based on a literature review. Findings indicate that this policy positively influences character development among students, enhancing their abilities in collaboration, autonomy, creativity, and ethical standards. This research aspires to illuminate the impact of Merdeka Bilajar's policy in the realm of theological education and facilitate more comprehensive student development, integrating intellectual, character, and spiritual dimensions.